2018
DOI: 10.1111/jcmm.13849
|View full text |Cite
|
Sign up to set email alerts
|

PKCα replaces AMPK to regulate mitophagy: Another PEDF role on ischaemic cardioprotection

Abstract: Both decreased autophagy positive regulator AMP activated protein kinase (AMPK) level and promoted mitophagy are observed in oxygen‐glucose deprivation (OGD) cardiomyocytes treated with pigment epithelium‐derived factor (PEDF). This contradictory phenomenon and its underlying mechanisms have not been thoroughly elucidated. Our previous study reveals that PEDF increases the protein kinase Cα (PKCα) and phospho‐PKCα (p‐PKCα) contents to promote mitophagy. Thus, we investigated the association between PKCα and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
10
1
Order By: Relevance
“…mTOR and AMPK belong to the serine/threonine protein kinase family, which plays a major role in maintaining blood glucose, body energy levels and homeostasis ( 34 ). mTOR is an upstream regulatory protein of the autophagy pathway, and increased activity of mTOR can inhibit downstream autophagy signaling proteins ( 35 , 36 ). Excessive mTOR activity in podocytes leads to dysregulation of autophagy, resulting in autophagic cell death, which plays a major role in the development of DN ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…mTOR and AMPK belong to the serine/threonine protein kinase family, which plays a major role in maintaining blood glucose, body energy levels and homeostasis ( 34 ). mTOR is an upstream regulatory protein of the autophagy pathway, and increased activity of mTOR can inhibit downstream autophagy signaling proteins ( 35 , 36 ). Excessive mTOR activity in podocytes leads to dysregulation of autophagy, resulting in autophagic cell death, which plays a major role in the development of DN ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…In cardiomyocytes, PEDF expression improved mitophagy to protect against hypoxic conditions by modulating the PEDF receptor (PEDF-R)/protein kinase C alpha (PKC-α) signaling pathway [ 40 ]. Although increased PKC-α expression by PEDF activates AMPK, which contributes to mitophagy in cardiovascular diseases [ 41 ], the effect of PEDF on mitophagy in the context of RPE degeneration is still unknown. We determined that the administration of PD-MSCs PEDF augmented the expression of both the autophagosome marker LC3 and the mitophagy marker PINK1 in H 2 O 2 -induced rat retinas ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies suggested that after the primary rat cardiomyocytes was administrated with OGD (oxygen-glucose deprivation) for 4 h, the cell survival rate decreased, LDH release was improved, and autophagy was activated [34]. The same method was adopted in this study to simulate ischemia and hypoxia in the border zone of myocardial infarction in rats, and the role of NR_027324 in the zone was studied.…”
Section: Discussionmentioning
confidence: 98%